2017
DOI: 10.1021/acsami.7b06793
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Additive Migration to Form Cathodic Interlayers in Organic Solar Cells

Abstract: Migration of additives to organic/metal interfaces can be used to self-generate interlayers in organic electronic devices. To generalize this approach for various additives, metals, and organic electronic devices it is first necessary to study the dynamics of additive migration from the bulk to the top organic/metal interface. In this study, we focus on a known cathode interlayer material, polyethylene glycol (PEG), as additive in P3HT:PCBM blends and study its migration to the blend/Al interface during metal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 43 publications
(82 reference statements)
0
13
0
Order By: Relevance
“…6,23,24 Time-of-flight secondary ion mass spectrometry (TOF-SIMS) and dynamic SIMS (DSIMS) provide a three-dimensional spatiallyresolved chemical profile; however, their lateral resolution is ∼ 50 nm-much larger than many morphological features-and the depth resolution from sputtering often must be correlated with a second measurement such as in-situ AFM. 6,7,15,23,35 Furthermore, because the material is sputtered, it generally creates fragments that make interpreting the resultant mass spectrum more difficult, and can have differences in sputtering efficiency for different materials. 23,37 Even with these limitations, SIMS is closest to a single measurement of chemical and morphological information that is widely used by the community, but still cannot answer many questions about system morphology because of its limited spatial resolution and fragmentation of molecular species.…”
mentioning
confidence: 99%
“…6,23,24 Time-of-flight secondary ion mass spectrometry (TOF-SIMS) and dynamic SIMS (DSIMS) provide a three-dimensional spatiallyresolved chemical profile; however, their lateral resolution is ∼ 50 nm-much larger than many morphological features-and the depth resolution from sputtering often must be correlated with a second measurement such as in-situ AFM. 6,7,15,23,35 Furthermore, because the material is sputtered, it generally creates fragments that make interpreting the resultant mass spectrum more difficult, and can have differences in sputtering efficiency for different materials. 23,37 Even with these limitations, SIMS is closest to a single measurement of chemical and morphological information that is widely used by the community, but still cannot answer many questions about system morphology because of its limited spatial resolution and fragmentation of molecular species.…”
mentioning
confidence: 99%
“…Migration and interlayer accumulation stop once a continuous interlayer is formed at the buried interface. 22 Current density-voltage (J-V) curves of OSCs incorporating different concentrations of HEG-DT and BDMT are plotted in Figure 4a and b, respectively. The average performance parameters of these devises are listed in Tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were recently reported for self-generated PEG interlayers in P3HT:PCBM devices with Al anodes. 22 It was suggested that the PEG interlayer shifted the "effective work function" of Al tuning the energetics at the interface. Indeed, the Voc and FF increase here are in good agreement with the SECO measurements (Figure 3c and 3d) and EWF estimation above.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations